2016
DOI: 10.31235/osf.io/htkn6
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Why People Overestimate Medicine's Value: The File Drawer Problem in Lay Health Communication

Abstract: *Objectives*. People often hold unduly positive expectations about theoutcomes of medical treatment. The objective to test the followingexplanation: People who have a positive outcome tend to tell more peopleabout their disease/treatment than people with poor or average outcomes.Akin to the file drawer problem in science, this systematically andpositively distorts the information available to others. *Design. *Acomparison of average health outcomes in clinical trials with averageoutcomes in online health produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…An analogous dynamic has been noticed for medical treatments. Studying reviews of cholesterol and weight loss treatments on the website amazon.com, de Barra [43] reported that "people who have a positive outcome tend to tell more people about their disease/treatment than people with poor or average outcomes”. If information A is “cholesterol treatment X is good” and information B is “cholesterol treatment X is bad”, even if the majority of individuals did not experience positive effects, information A will be more likely to be shared, and may appear to be more common.…”
Section: Empirical Cases Of Variant Overrepresentation and Model Biasesmentioning
confidence: 99%
“…An analogous dynamic has been noticed for medical treatments. Studying reviews of cholesterol and weight loss treatments on the website amazon.com, de Barra [43] reported that "people who have a positive outcome tend to tell more people about their disease/treatment than people with poor or average outcomes”. If information A is “cholesterol treatment X is good” and information B is “cholesterol treatment X is bad”, even if the majority of individuals did not experience positive effects, information A will be more likely to be shared, and may appear to be more common.…”
Section: Empirical Cases Of Variant Overrepresentation and Model Biasesmentioning
confidence: 99%